Nghiên cứu điều chế chế phẩm chống oxi hóa từ rễ thổ phục linh (Simila glabra Roxb.) của Việt Nam - Vượng, Nguyễn Quốc; Thanh Vân, Trịnh Thị; Chiến, Vũ Văn; Hằng, Phạm Thị; Cường, Phạm Văn (Vietnam Journal of Chemistry, 2015)
An antioxidant functional food from the root of Smilax glabra Roxb. of Vietnam (TPL-As40) was prepared, by using the purified EtOH extract which contains high astilbin content (46.1 %) as determined by HPLC analysis. The antioxidant activity of this functional food was evaluated by different methods: DPPH assay for free radical scav enging capacity, MDA assay for inhibition of lipid peroxidation and MTT assay for hepato protective effection H2O2-injured mouse hepatocytes. Accordingly, the TPL-As40 had significant antioxidant property with SC50 value of 19.8 µg/ml (DPPH assay), IC50 value of 9.32 µg/ml (MDA assay) and EC50 value of 20.95 µg/ml (MTT assay). The toxicity evaluation in mice indicated that theTPL-As40 product was safe for use as functional food according to OECD.